Evaluating the Potential of Container-Based Sanitation : Sanergy in Nairobi, Kenya - World Bank (World Bank, Washington, DC, 2019)
This case study examines the container-based sanitation (CBS) service provided by Sanergy and how its business model fits overall in Nairobi as well as specifically in informal settlements there. Sanergy’s basic business concept is to provide safe sanitation to low-income residents of informal settlements in Nairobi and to create a sustainable value chain that converts feces into premium reuse products for agriculture. Sanergy provides single-cubicle, branded Fresh Life Toilets (FLTs) to franchisees for a fee and collects the excreta from the toilets on a frequent basis (daily or every two or three days). Satisfaction expressed by customers with Sanergy’s toilets was high and users of Sanergy’s toilets are paying much the same rates as they would for other toilet options. Overall, the FLT operation shows promise to provide a highly cost-effective sanitation solution at scale and the evolving policy landscape and significant investment by Sanergy and others has radically changed the status of CBS in a short time. Sanergy plans to scale significantly to serve as many as 500,000 people in its existing areas of operation, an ambitious expansion plan that will warrant further study and monitoring.